Peningkatan Literasi Membaca dan Literasi Keuangan Siswa Sekolah Dasar Melalui Program Edukasi Interaktif di SDN Badean 3 - Sitta Kurrata A'yun; Fahimatul Anis; Faidiyah Ramdhaniyah; Anabella Azahratul Chriska; Aditya Pratama; Cantika Nathania Sabela; Ayu Shakina Isabella; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service program aimed to enhance elementary school students’ reading literacy and financial literacy through an interactive, enjoyable, and contextual educational approach. The program was implemented at SDN Badean 03, Bondowoso District, Bondowoso Regency, involving 36 students from grades 1 to 6. A descriptive qualitative approach was employed, with data collected through observation, interviews, documentation, as well as pre-tests and post-tests. Reading literacy activities were focused on grades 1 and 2 through read-aloud sessions and vocabulary games, while financial literacy activities targeted grades 3 to 6 through the creation of piggy banks from recycled materials and saving simulations. The results indicated an improvement in basic reading skills, as reflected by a shift in students’ reading ability categories, with the percentage of students in the moderately fluent category increasing from 22.22% in the initial condition to 33.33% in the final condition, accompanied by a decrease in the less fluent category. These findings suggest that the literacy interventions were effective in supporting students with lower reading proficiency to progress to higher levels. In addition to cognitive improvement, the program also had positive effects on students’ affective aspects, including increased self-confidence, responsibility, and learning enthusiasm. Therefore, this integrated literacy program is effective in fostering a reading culture and enhancing financial awareness among students from an early age.